Essential Oils of Three Ziziphora L. Taxa from Turkey and Their Chemotaxonomy - Kilic, Omer; Bagci, Eyup (Asian Journal of Chemistry, 2013)
The essential oil aerial parts of Ziziphora clinopodioides Lam., Z. persica Bunge and Z. tenuior L. were investigated by GC and GC-MS. The yield of oils are ca. 0.30, 0.35 and 0.40 mL/100 g, respectively. Thirty seven, fourty five and thirty six compounds were identified representing 90.20, 93.12 and 92.69 % of the oil, respectively. Pulegone (20.18 %), piperitone (14.28 %) and limonene (10.66 %) in Z. clinopodioides, pulegone (33.27 %), b-pinene (5.75 %) and piperitone (5.68 %) in Z. persica, pulegone (30.00 %) and 1,8-cineole (9.65 %) were identified as major components in Z. tenuior. The chemical distribution of the essential oil compounds in the genus pattern were discussed in means of chemotaxonomy and natural products. In conclusion, pulegone and piperitenone derivatives are characteristic and represent excellent chemotaxonomical markers for Ziziphora taxa.